2021
DOI: 10.14311/ap.2021.61.0364
|View full text |Cite
|
Sign up to set email alerts
|

Modified Possibilistic Fuzzy C-Means Algorithm for Clustering Incomplete Data Sets

Abstract: A possibilistic fuzzy c-means (PFCM) algorithm is a reliable algorithm proposed to deal with the weaknesses associated with handling noise sensitivity and coincidence clusters in fuzzy c-means (FCM) and possibilistic c-means (PCM). However, the PFCM algorithm is only applicable to complete data sets. Therefore, this research modified the PFCM for clustering incomplete data sets to OCSPFCM and NPSPFCM with the performance evaluated based on three aspects, 1) accuracy percentage, 2) the number of iterations, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Furthermore, the determination and should be done simultaneously. However, we choose to initiate to counting [46] . There are several advantages with initializing and terminating in in terms of convenience, convergence speed, and storage [40] .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the determination and should be done simultaneously. However, we choose to initiate to counting [46] . There are several advantages with initializing and terminating in in terms of convenience, convergence speed, and storage [40] .…”
Section: Methodsmentioning
confidence: 99%
“…It is necessary to wait until enough observations are obtained to carry out the imputation, which is time consuming and undermines its effectiveness [28]. For the fourth method, previous studies have shown that some algorithms, such as decision trees, support vector machines, fuzzy algorithms, etc., can effectively process missing values [29][30][31]. Among them, the RF model stands out due to its applicability in the case of missing data [32].…”
mentioning
confidence: 99%